ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SESUDAH PENERAPAN PSAK 73 ATAS SEWA PADA PERUSAHAAN SEKTOR JASA NON KEUANGAN YANG TERDAFTAR DI BEI - Gemilang Emas (2022)
This study was conducted to see the difference in financial performance before and after the application of PSAK 73. Financial performance using liquidity ratios, solvency ratios and profitability ratios. The liquidity ratio is proxied by the current ratio, solvency is proxied by the debt to asset ratio, debt to equity ratio and long term debt to equity ratio and the profitability ratio is proxied by return on assets and return on equity. Each financial performance variable is compared before and after the company implements PSAK 73. The object in this study is a non-financial service company listed on the Indonesia Stock Exchange. The sample was selected using a purposive sampling technique so that the sample obtained was 325 company samples. The software or tool used to test the hypothesis is SPSS version 26. The results of this study indicate that 1) There is no significant difference in the liquidity ratio between before and after the application of PSAK 73; 2) There is a significant difference in the solvency ratio between before and after the application of PSAK 73; 3) There is a significant difference in the profitability ratio between before and after the implementation of PSAK 73.